Robust formation tracking control of mobile robots via one-to-one time-varying communication - Dasdemir, Janset; Loria, Antonio (TAYLOR & FRANCIS LTD, 2014)
We solve the formation tracking control problem for mobile robots via linear control, under the assumption that each agent communicates only with one 'leader' robot and with one follower, hence forming a spanning-tree topology. We assume that the communication may be interrupted on intervals of time. As in the classical tracking control problem for non-holonomic systems, the swarm is driven by a fictitious robot which moves about freely and which is a leader to one robot only. Our control approach is decentralised and the control laws are linear with time-varying gains; in particular, this accounts for the case when position measurements may be lost over intervals of time. For both velocity-controlled and force-controlled systems, we establish uniform global exponential stability, hence consensus formation tracking, for the error system under a condition of persistency of excitation on the reference angular velocity of the virtual leader and on the control gains.
Keywords: mobile robots; formation control; tracking control; consensus; FOLLOWER FORMATION CONTROL; TRAJECTORY TRACKING; SYSTEMS; PERSISTENCY; EXCITATION; STABILITY; Automation & Control Systems